2016
DOI: 10.1177/0972150916630454
|View full text |Cite
|
Sign up to set email alerts
|

Role of Country-specific Factors on Capital Structure Decision—Evidence from Sri Lankan Listed Firms

Abstract: Capital structure is a very significant area in strategic financial decision making of firms. Several factors, both internal and external, influence a firm's choices of capital structure. It is found that the research on this topic has mainly covered industrialized countries. Very little is known about the decision-making process on capital structure of firms in developing countries. The aim of this study is to investigate for the period 2000-2013, using panel data, the role of long-run effect of country-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…It has important theoretical as well as practical implications for business activities and academia. Furthermore, most studies focus on well-developed financial markets and very little is known about corporate FF in less developed financial markets and emerging markets (Buvanendra et al , 2016). The present study contributes to filling this gap in the literature and provides a more practical and functional framework to assess the FF of firms located in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has important theoretical as well as practical implications for business activities and academia. Furthermore, most studies focus on well-developed financial markets and very little is known about corporate FF in less developed financial markets and emerging markets (Buvanendra et al , 2016). The present study contributes to filling this gap in the literature and provides a more practical and functional framework to assess the FF of firms located in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bastos et al (2009) found no significant impact of inflation on leverage. Buvanendra et al (2016) investigated the impact of country-specific factors, such as rate of inflation, size of capital market, corporate tax rate, civil unrest, gross domestic product (GDP) growth and prime lending rate, on capital structure choices among Sri Lankan firms listed in the Colombo Stock Exchange. They state that no selected country-specific variables have any direct influence on the capital structure decision of firms.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Companies can use funding sources that come from capital or debt, to realize this increase in their businesses. This means that there is a tendency for an increase in the companies' debt, due to an increase in the economy (Gajurel, 2011;Buvanendra, Sridharan and Thiyagarajan, 2016;Rodrigues et al, 2017;Bokpin, 2009;Mahmud, 2003). Therefore, capital structure is one of the important policies for management in the corporate financial management (Nguyen, Bui, & Pham, 2019;Nguyen & Nguyen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reveal a positive relationship between macroeconomic factors and CFF of firms, others suggest a negative relationship (Khémiri and Noubbigh, 2018). Conversely, certain studies have also identified an insignificant effect of macroeconomic variables on CFF of firms (Buvanendra et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%